2006
DOI: 10.1097/01.cad.0000236307.20339.b4
|View full text |Cite
|
Sign up to set email alerts
|

Human and murine macrophages mediate activation of MEN 4901/T-0128: a new promising camptothecin analogue–polysaccharide conjugate

Abstract: MEN 4901/T-0128 is a new cytotoxic prodrug constituted by the camptothecin analogue T-2513 bound to carboxymethyl dextran through a triglycine linker. MEN 4901/T-0128 was designed to target the active camptothecin at the tumour site. MEN 4901/T-0128 is weakly cytotoxic in vitro and thus T-2513 must be released from the conjugate to become active. Here, we demonstrated that human purified cathepsin B releases T-2513 from MEN 4901/T-0128 at pH values ranging from 3 to 5. pH dependency of this reaction suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The liver, spleen and lymph nodes, however, also showed significant uptake, suggesting recognition by the reticuloendothelial system, which was later investigated and confirmed in studies involving macrophage-mediated activation of T-0128. 289, 290 …”
Section: Macromolecular Architectures For Passive Drug Deliverymentioning
confidence: 99%
“…The liver, spleen and lymph nodes, however, also showed significant uptake, suggesting recognition by the reticuloendothelial system, which was later investigated and confirmed in studies involving macrophage-mediated activation of T-0128. 289, 290 …”
Section: Macromolecular Architectures For Passive Drug Deliverymentioning
confidence: 99%
“…Figure 6 shows that in the culture medium T‐2513 is present at a concentration able to kill A2780 cells. T‐2513 release from delimotecan depends on Cathepsin B activity 11. The activity of this enzyme into Me 15392 cells is at least 5–6‐fold higher than that present in differentiated THP‐1+PMA monocytic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Because macrophages are cells specialized in phagocytose activity and they are able to phagocytose delimotecan,10, 11 we evaluated the percentage of macrophage cells recruited into the tumor tissue. Figure 7 Panels a – d , shows that in the tumor nodule generated by Me 15392, there is a significant amount of macrophages evaluated by FACS analysis with F4/80 staining (27%) a macrophage‐restricted receptor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies suggested that delimotecan can permeate and accumulate in tumor tissue and is cleaved to T-2513 by cathepsin B, which is overexpressed in tumors. These studies further showed that tumor-associated macrophages may play a key role in the uptake of delimotecan and cleavage and local release of T-2513 (12,13). T-2513 can be metabolized to the CPT analogues, T-0055, T-1335, T-3921, and SN-38 (the active metabolite of CPT-11), which is glucuronidated to SN-38 glucuronide (SN-38G; Fig.…”
mentioning
confidence: 99%